2004
DOI: 10.2460/ajvr.2004.65.741
|View full text |Cite
|
Sign up to set email alerts
|

Objective determination of pelvic movement during hind limb lameness by use of a signal decomposition method and pelvic height differences

Abstract: Pelvic height differences and signal decomposition of pelvic movement can be used to objectively evaluate hind limb lameness in horses over a large number of strides in clinical and research settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 18 publications
3
83
0
1
Order By: Relevance
“…The proposed method can therefore be used for the analysis of pathological gait, where features are commonly independent of the exact foot contact (e.g. Buchner et al, 1996;Peham et al, 1996;Uhlir et al, 1997;Audigie et al, 2002;Keegan et al, 2003Keegan et al, , 2004Kramer et al, 2004). Since none of the features expressed as % stride was dependent on Froude Number or stride duration, no systematic changes of the foot contact estimate relative to the gait cycle should be expected with increasing trotting speed.…”
Section: Discussionmentioning
confidence: 95%
“…The proposed method can therefore be used for the analysis of pathological gait, where features are commonly independent of the exact foot contact (e.g. Buchner et al, 1996;Peham et al, 1996;Uhlir et al, 1997;Audigie et al, 2002;Keegan et al, 2003Keegan et al, , 2004Kramer et al, 2004). Since none of the features expressed as % stride was dependent on Froude Number or stride duration, no systematic changes of the foot contact estimate relative to the gait cycle should be expected with increasing trotting speed.…”
Section: Discussionmentioning
confidence: 95%
“…Horses were evaluated for lameness by use of a computer-assisted kinematic gait analysis and a lameness-detection algorithm 19,22 before and after induction of transient lameness in each foot. Order of limb selection for induction of lameness was randomized.…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6][7] Computer-assisted kinematic gait analysis has been used to establish objective lameness evaluation techniques that could be adapted for clinical use. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Studies 13,14,18-23 have revealed that kinematic evaluation of vertical motion of the head and pelvis in relation to vertical movement of the feet on 1 side of the body is all that is required to detect lameness and differentiate the affected limb.…”
mentioning
confidence: 99%
“…All data collected were transmitted in real time to a portable computer via bluetooth, where a specific software makes the data analysis, according to the study by Kramer et al [11]. The following variables were analyzed: a1/a2 of the fore and hind limbs (relation between the amplitude of the vertical movement of the head or pelvis produced by the lameness and the amplitude of the basal movement of the head or pelvis); DIFFMAX, and DIFFMIN of the forelimbs and the hind limbs (mean and standard error; difference between the highest or lowest point reached by the head or pelvis after weight support of the right forelimb or right hind limb and the same point reached by the left forelimb or left hind limb, respectively).…”
Section: Data Collection and Analysismentioning
confidence: 99%